Named data for mobile AdHoc networks - Pereira, Ana Filipa (2016)
For the needs of future Internet, many researchers are proposing a paradigm shift towards a new information-centric approach. The Named-Data Networking (NDN) is one these proposals. Instead of addresses, packets should use only names, either expressing interest on specific information or naming the data content carried in. Applying the NDN model in a mobile ad-hoc network can greatly simplify the routing, since there is no need for global addresses and all nodes in the network can cache data packets.In this paper we propose a new strategy, called MultiPoint Relay (MPR) Strategy, targeted to minimize redundancy in Interest and Data packet forwarding in Ad-Hoc NDN networks. Interest packets sent by each node are only retransmitted by a subset of selected relay neighbors, as in OLSR. A time delay is also used to detect and prevent duplicated transmissions. Data packets can either be forwarded using the reverse path or by using similar delay technique in case of topology changes. The proposed strategy was implemented in ndnSIM simulator and compared with related works. Obtained results show that the strategy is effective in improving interest satisfaction ratio with reduced network overhead.